Evaluation of quality level in managing the development of industrial enterprises - Raiko, Diana; Podrez, O.; Cherepanova, V. O.; Fedorenko, I. A.; Shypulina, Yu. S. (Технологический центр, 2019)
The research focuses on the substantiation of theoretical aspects and practical support for assessing the quality level of managing enterprises development taking into account the influence of the external and internal environment. The conceptual apparatus for estimation of quality development of enterprise management was refined, which makes it possible to determine reasonably the level of management according to the generally known elements (economic, social and ecological) that are proposed to be supplemented with an energy component. A new conceptual approach to the procedure of evaluation of the quality of development management by levels, the stages of which are proposed to expand by: the formation of the database by levels of management (state, regional), choice and evaluation of indicators by components of development and spheres of activity, development of the tools for management improvement. The integrated indicator has been proposed, which differs from the existing ones by the fact that it estimates the quality of development management, rather than the development level. In contrast to the previously proposed ones, the integrated indicator takes into account the influence of external environment by the components of development and of the internal environment – by the areas of activity for each component. That is why it has practical significance, since it allows performing monitoring and detecting the negative influence of management on the enterprise development. Taking coke plants as an example, the structures of the indicators that characterize the management quality were determined. A large number of indicators were reduced by the method of expert assessments, which increases the validity of the choice. Indicator estimates were constructed solely based on relative indicators (indices), which improves consistency. Using the integrated method, the estimation of the indicators by individual components and on the whole was performed. The scale for evaluation of the quality level of enterprise development management was constructed using the Harrington function. The new approach to assessing the quality of the enterprise development management and a complex of mathematical support will lead to the uniform economic, social, environmental and energy development of enterprises.

Роботу присвячено обґрунтуванню теоретичних аспектiв та практичного забезпечення оцiнки якiсного рiвня управлiння розвитком пiдприємств з урахуванням впливу зовнiшнього та внутрiшнього середовища. Уточнено понятiйний апарат щодо оцiнки якiсного розвитку управлiння пiдприємствами, який дозволяє обґрунтовано визначати рiвень управлiння за загальновiдомими складовими (економiчної, соцiальної та екологiчної), до яких запропоновано додати енергетичну складову. Побудовано новий концептуальний пiдхiд до процедури оцiнки якостi управлiння розвитком за рiвнями, етапи якої запропоновано розширити за: формуванням бази даних за рiвнями управлiння (державний, регiональний), вибiр та оцiнка iндикаторiв за складовими розвитку та сферами дiяльностi, розробка iнструментiв щодо покращення управлiння. Запропоновано iнтегральний показника, який вiдрiзняється вiд iснуючих тим, що оцiнює якiсть управлiння розвитком, а не рiвень розвитку. На вiдмiну вiд запропонованих ранiше iнтегральний показник враховує вплив зовнiшнього середовища за складовими розвитку та внутрiшнього – за сферами дiяльностi по кожнiй складовiй. Тому, має практичну значимiсть, оскiльки стає можливим проводити монiторинг та виявляти негативний вплив управлiння на розвиток пiдприємства. На прикладi коксохiмiчних пiдприємств визначено склад iндикаторiв, якi характеризують якiсть управлiння. Велику кiлькiсть iндикаторiв скорочено за допомогою методу експертних оцiнок, що пiдвищує обґрунтованiсть вибору. Iндикаторнi оцiнки побудовано виключно за вiдносними показниками (iндексами), що покращує узгодженiсть. За iнтегральним методом проведена оцiнка iндикаторiв за окремими складовими та у цiлому. За функцiєю Харрiнгтону побудовано шкалу оцiнки якiсного рiвня управлiння розвитком пiдприємств. Новий пiдхiд щодо оцiнки якостi управлiння розвитком пiдприємств та комплекс математичного забезпечення приведе до рiвномiрного економiчного, соцiального, екологiчного i енергетичного розвитку пiдприємств.
Keywords: estimation of development management level; system of indicator estimates; components of development; integrated indicator; estimation scale; оцiнка рiвня управлiння розвитком; система iндикаторних оцiнок; складовi розвитку; iнтегральний показник; шкала оцiнки